(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The article reveals the features of the methodological justification of the features of the functioning of the biogas plant methane tank. The idea of the scientific work is to use waste and by-products of processing industries, which will be implemented in rural areas, as co-substrates in methane fermentation of livestock by-products, which will increase the biogas yield and increase the efficiency of biogas production and solve the problem of disposal of these wastes. As a result of the analysis of existing mathematical models of the biogas production process, it was established that under conditions of ideal substrate mixing and constant temperature, the main factors affecting the course of methanogenesis are the process time, as well as the concentration of methanogens, substrate nutrients and metabolic products (biogas). The mathematical model of the biogas production process generally contains a system of differential equations, the joint solution of which allows, under given initial conditions, to find the change in time of the concentration of methanogens, substrate nutrients and metabolic products (biogas).